Detection and investigation of chirping Alfvén eigenmodes with heavy ion beam probe in the TJ-II stellarator. (29th June 2018) - Melnikov, A.V.; Ascasibar, E.; Cappa, A.; Castejón, F.; Eliseev, L.G.; Hidalgo, C.; Khabanov, P.O.; Kharchev, N.K.; Kozachek, A.S.; Krupnik, L.I.; Liniers, M.; Lysenko, S.E.; et al.
Abstract: Alfvén eigenmodes were studied in the low magnetic shear flexible heliac TJ-II NBI-heated plasmas by heavy ion beam probe (HIBP), which is capable to measure simultaneously the oscillations of the plasma electric potential, density and poloidal magnetic field in the bulk plasmas. The L-mode hydrogen plasma was investigated at various magnetic configurations with rotational transform ι ( a )/2 π 1.5–1.6. Co-, counter- and balanced beam injection were explored. The present study was focused on the high-frequency chirping modes with 250 kHz < f AE < 350 kHz at the low-density = (0.5–0.7) × 10 19 m −3 NBI-heated plasmas without auxiliary ECRH. Here we report the observation of the various types of chirping modes, differing by frequency, radial location, amplitude and shape of the frequency dependence on time (burst pattern). Remarkably, the same mode may evolve, changing its burst pattern in the same frequency range in the single discharge. The radial scan of the HIBP sample volume indicates the radial evolution of the potential and density perturbation during the single frequency burst of the chirping mode. The individual burst of the chirping-up mode can propagate outward with volume-averaged radial velocity ≈70 m s −1 . The frequency raise during the burst is in line with Alfvén frequency dependence on density, which decreases over the propagation area.